PERAN PENDIDIKAN AGAMA ISLAM DALAM MENGHADAPI TANTANGAN GLOBAL - Abdullah Zaini (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
Islamic Religious Education is a deliberate and planned effort to prepare students to know, understand, and practice the teachings of Islam in everyday life. This education aims to shape students into human beings who believe and fear Allah SWT, have noble morals, are healthy, intelligent, creative, independent, and responsible. Islamic Religious Education not only teaches knowledge about religion, but also how to direct students to have the qualities of faith, piety, and noble morals. Thus, the target of Islamic Religious Education is the formation of students' personalities so that they have strong faith and piety, and their lives are always decorated with noble morals wherever they are, and in various fields of life. The purpose of this study is to explore and provide an overview of the role of Islamic Religious Education in facing global challenges. This study uses a descriptive research method with a literacy study from various related sources. The results of this study are the discovery of the concept of the role of Islamic Religious Education in facing various global challenges.